Remediation: Understanding Academic Integrity - Chaudhuri, Anita (Canadian Perspectives on Academic Integrity, 2021)
Recent data on academic misconduct shared by some Canadian post-secondary institutions have reported that the numbers have doubled (CBC News, 2020; CTV News Regina, 2021) or increased significantly by up to 38% (UCalgary News, 2020). These instances establish academic integrity as a current and critically important topic for institutions as well as the scholarship of teaching and learning. Discussions in this ethical area of concern focus on ways to convince students “to behave as honest and responsible members of an academic community” (UBC, Academic Honesty and Standards) during an emergency situation (such as, the pandemic) and avoid disciplinary action. Researchers in academic integrity have noted that it is essential that students are given ample opportunities to understand the concept. In this presentation, we, two undergraduate students and an instructor: (i) share some of the ways in which teaching and learning practices changed in an online composition studies classroom; (ii) discuss how these changes addressed the expectations of academic integrity; and (iii) showcase an example from a university-wide contest on academic integrity as an opportunity to remediate personal understanding of the topic and contribute towards a community service initiative.